Consumer perceptions of the use of nondegradable plastic packaging and environmental pollution: A review of theories and empirical literature - Virimai Victor Mugobo; Herbert Ntuli; Chux Gervase Iwu (Journal of Risk and Financial Management, 2022)
Studying people's perceptions of their attitudes and behaviour toward the use and inappropriate disposal of plastics is necessary because it helps explain the meaning of sustainable environmental behaviour in the context of African countries. Formulating appropriate behavioural change interventions may lead to a shift in people's behaviour in terms of plastic consumption if they become aware of the environmental risk of plastics. Using a qualitative review of literature, relevant materials for this paper were identified using a search strategy that involved keywords and databases. Previous empirical studies employed several theoretical frameworks. However, inconsistences in the use and definition of variables, make comparing the results of these studies difficult. Although the literature is growing, more empirical evidence is still needed to understand the drivers of people's perceptions toward unsustainable environmental behaviour in the context of African countries and to formulate appropriate behavioural change interventions. A review of the literature determined four broad drivers of people's perceptions toward unsustainable environmental behaviour. These include policy or institutional variables, product and market attributes, community variables, and individual characteristics. Additionally, we offer a consolidated conceptual framework for analysing consumer perception in relation to the use of nondegradable plastics and environmental pollution and identify the drivers of people's perceptions. Policy implications for developing countries as well as future research directions are flagged.
Keywords: 650; attitudes; behaviour; consumer perceptions; degradable and nondegradable plastic packaging; environmental pollution